How do you burp in space? : and other tips every space tourist needs to know - Goodman, Susan E., 1952-; Slack, Michael, 1969- (New York : Bloomsbury Pub., 2013)
"A non-fiction travel guide to space tourism that includes information about accommodations, attractions, and more." --
Keywords: Manned space flight -- Juvenile literature; Interplanetary voyages -- Juvenile literature; Space tourism -- Juvenile literature